The Effect Of Avocado Fruit On The Nutritional Needs Of Pregnant Women Trimeter I At Pmb Tati Hidayat Jati Rahayu Bekasi In 2022 - Nursila Nursila; Maryati Sutarno (International Journal of Health and Pharmaceutical (IJHP), 2023)
Pregnant women most commonly experience anemia during the first trimester of pregnancy as a result of poor diet, which causes nausea and a lack of appetite. Chronic energy deficiency (CED) in pregnant women is caused by a long-lasting lack of energy intake in the mother, causing health problems. Pregnant women's nutritional intake has a significant impact on fetal growth during pregnancy, the incidence of low birth weight during delivery, and the baby's growth and development. Avocado (Persea americana) is a fruit that is very well known and popular with the public. Apart from having a delicious taste and soft texture, avocados also have several health benefits. The main components of avocados are carotenoids, fatty acids, minerals, phenolics, phytosterols, proteins, and many vitamins. Avocado is a fruit that is rich in vitamin A. Vitamin A has a role in erythropoiesis related to its function of synthesizing protein so that it will affect the growth of bone cells. Bone marrow is the site of the formation of erythrocytes. Vitamin A is needed in several essential processes in the body, such as metabolism, hematopoiesis, and erythropoiesis; it also regulates cell differentiation and plays a role in the immune system.The approach used in this research is experimental research. Experimental research is research that is carried out by manipulating, and it aims to determine the effect of manipulation on the observed individual's behavior. Manipulation carried out can be in the form of certain situations or actions given to individuals or groups, and after that, the effect can be seen. This experiment was conducted to determine the effects of a treatment given intentionally by the researcher. Giving this treatment is a peculiarity of experimental research compared to other studies. The results showed that there was a significant relationship between giving avocado fruit and improving the nutrition of first-trimester pregnant women, as indicated by the p value of 0.000. This is supported by research data showing that giving avocado fruit increases nutrition more, namely by as much as 70%, while not regularly consuming a lot of avocado fruit does not increase nutrition by 30%.